Optimization of a co2 backpulsing method for increasing the permeate flux in cold microfiltration of skim milk: a pilot-scale study - Tan, Teng Ju; Moraru, Carmen (2014)
The major challenge associated with cold microfiltration (MF) of skim milk is the decrease in permeate flux, caused by fouling. To address this, a novel CO2 backpulsing technique capable to counteract membrane fouling was developed and optimized. Five portable CO2 backpulsing ports were attached to the membrane housing. Five different combinations of CO2 backpulsing frequencies and durations were tested. The MF experiments were performed at a temperature of 6 ± 1°C, a cross-flow velocity of 3.8 m/s and a transmembrane pressure of 83 kPa. A series of 45 min experiments were first performed. The combination of 3 ports at 120s frequency with 1s duration (120s/1s) produced the highest flux: 46.09 L/m2h at 45 min. In a series of three hour MF runs, permeate flux from the treatments with 3 ports at 120s/1s and 5 ports at 180s/1s was significantly higher than for the control. After 3 h, the flux for the control was 25.85 ± 0.99 L/m2h, while for the optimized CO2 backpulsing experiment, a flux of 30.02 ± 0.48 L/m2h was obtained. In addition, a smaller drop in flux was observed for the optimized CO2 backpulsing run (15.57% after 3 h) as compared to the control (29.83% after 3 h). Furthermore, the protein transmission into permeate was also the highest in treatment of the 3 ports at 120s/1s. Another study was conducted to evaluate the performances of optimized MF and control at a higher cross-flow velocity (6 m/s). The permeate flux after 3 h for the optimized MF was 82.32 ± 4.42 L/m2h while for control was 71.39 ± 4.21 L/m2h. The developed CO2 backpulsing technique is an efficient and affordable solution to mitigate fouling and thus increase the permeate flux in cold MF of skim milk, and could also be applied to other cold microfiltration processes, including filtration of juice, or heat sensitive fluids that require cold processing.